Analysis of Computed Tomography Dose Index (CTDI) And Dose Length Product (DLP) Dose Values On Non-Contrast Head, Chest And Abdominal CT Scan Examination At RSUD Ulin Banjarmasin - Fitriana, Kartika Puspa; Indrati, Rini; Kurniawan, Andrey Nino (Politeknik Kesehatan Kemenkes Jakarta II, 2023)
Background: CT scans produce the largest dose of radiation compared to other radiology modalities. The parameters for measuring the amount of radiation dose from the CT Scan aircraft are the Computed Tomography Dose Index (CTDI) and the Dose Lenght Product (DLP). One form of Bapeten supervision in controlling radiation protection is to optimize the Diagnostic Raference Level (DRL). At RSUD Ulin Banjarmasin, the CT Scan modality has never been measured for CT Scan dose on CT Scan examination of the Head, Thorax and Abdomen Non Contrast which are the most frequent examinations. Dosage parameters are important to see the values exposed to the patient. The purpose of this study was to determine the amount of radiation dose of patients on CT Scan examination of the Head, Thorax and Non-Contrasting Abdomen. Method: The research design used is quantitative descriptive. The method of collecting data is observational and uses secondary data. Data processing uses the descriptive hypothesis test method one sample t-test, by analyzing the value of radiation dose and comparing the DRL value set by Bapeten as a means to monitor the dose given α=0.05. Results: Dose values for CT Scan of Non Contrast Head 33.90±3.66 mGy for CTDIvol and 933.07±415.63 mGy.cm for DLP. CT Scan Thorax Non Contrast 5.83±1.90 mGy for CTDIvol and 179.80±63.72 mGy.cm for DLP. Non Contrast Abdominal CT Scan 10.88±2.30 mGy for CTDIvol and 528.70±137.75 mGy.cm for DLP. Conclusion: The dose value at RSUD Ulin Banjarmasin in each CT Scan examination of the Head, Thorax and Abdomen Non Contrast is still below the National DRL value set by BAPETEN.